The Impact of an Ego Depletion Manipulation on Performance-Based and Self-Report Assessment Measures. (October 2016) - Charek, Daniel B.; Meyer, Gregory J.; Mihura, Joni L.
We investigated the impact of ego depletion on selected Rorschach cognitive processing variables and self-reported affect states. Research indicates acts of effortful self-regulation transiently deplete a finite pool of cognitive resources, impairing performance on subsequent tasks requiring self-regulation. We predicted that relative to controls, ego-depleted participants' Rorschach protocols would have more spontaneous reactivity to color, less cognitive sophistication, and more frequent logical lapses in visualization, whereas self-reports would reflect greater fatigue and less attentiveness. The hypotheses were partially supported; despite a surprising absence of self-reported differences, ego-depleted participants had Rorschach protocols with lower scores on two variables indicative of sophisticated combinatory thinking, as well as higher levels of color receptivity; they also had lower scores on a composite variable computed across all hypothesized markers of complexity. In addition, self-reported achievement striving moderated the effect of the experimental manipulation on color receptivity, and in the Depletion condition it was associated with greater attentiveness to the tasks, more color reactivity, and less global synthetic processing. Results are discussed with an emphasis on the response process, methodological limitations and strengths, implications for calculating refined Rorschach scores, and the value of using multiple methods in research and experimental paradigms to validate assessment measures.